An Investigation in to the Impact of Iranian EFL Teachers´ Creative Strategy and Learners' Language Improvement - Tashakori, sakine; Mirzaee, Abolghasem; Rahimi, Mohammad; Rahmanian, Mojtaba (IJRDO- Journal of Educational Research, 2018)
This study aimed to determine if teachers’ application of creative strategies within language classrooms would enhance the quality of learning foreign languages. In the first phase, ELTCQ questionnaire was given to a total of 70 teachers, to see whether they use creative strategies or not. In the second phase, a total of 30 intermediate EFL students were randomly assigned to two equal groups of experimental and control. The findings revealed that teachers’ creativity and the application of creative techniques in classrooms significantly affect students’ language achievement.